STRATEGI KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN DI SEKOLAH DASAR - Yasmin Hazizah, Ismi; Roshanza Ikhsani, Chania; Putri, Andini; Ananda, Rizki (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to analyze the principal's strategy in improving quality, especially in elementary schools. The research method used by researchers is using Syistematic Literature Review (SLR) with the following steps: identifying research questions, searching for literature materials, selecting literature materials, analyzing and interpreting data, preparing draft articles, and disseminating results. This study uses 20 relevant articles that have been analyzed from the selection of 30 articles obtained from various sources with publication years ranging from 2014 to 2023. The center of study in this research is about the principal's strategy and the implications of the strategy for schools in improving the quality of education in elementary schools. The results showed that. 1) the strategies produced by school principals to achieve the quality of education vary depending on the needs, conditions, supporting factors and inhibiting factors in related elementary schools; 2) the implications of the principal's strategy that has been prepared have a good impact on the quality of education, both in human resources (educators, students, school staff), academic and non-academic achievements of students, facilities, school infrastructure and relationships with the community; 3) in general, the strategy used by principals in elementary schools is to improve the quality of teaching staff (teachers) first. The conclusion of this study is that the principal is the main actor who plays an important role in improving the quality of education in elementary schools. By understanding his role, the principal conducts planning by developing various strategies that have been adjusted to the needs of the school. The research suggestion is that every principal in elementary school should have an awareness of the importance of improving the quality of education by paying more attention to the quality of educators and students. Keywords: education quality, principals, strategies